Problems and Prospects of Fish Fry Trade in Jessore District of Bangladesh - Rahaman, MM; Sayeed, MA; Paul, A; Nahiduzzaman, M (Progressive Agriculture, 2014)
A study was conducted to investigate the existing system of fry trade and different problems and prospects associated with this enterprise in Jessore district. A total of 82 hatchery operators and nursery owners were interviewed using a structured questionnaire. In the study period 4211.5 kg hatchling were produced in 85 hatcheries in this area of which 80% were reared in the same area. Average price of per kg hatchling were Indian major carps- Tk.1200 to 1800, Chinese carp Tk. 1200 to 1600 and Thai sharpunti and pungus- Tk. 900 to 1200. A total 1621 lacs of 1-4" sized fry was produced during the study period. Among them Indian major carp 864.3 lacs (53.32%), Chinese carp 621.9 lacs (38.36%), Thai sharpunti and pangus 134.8 lacs (8.32%). The fry mortality was observed 24 % (± 1.92) due to improper management. The aratdar and middlemen were controlling the marketing system. As a consequence, fry traders and nursery operators have been facing several problems in this business. The main constrains were lack of capital (35%) followed by lack of technical knows-how (27%) faced by fry traders. The nursery operators faced the problems like lack of capital (31%), high lease value (25%), high price of production inputs (17%), terrorism (12%), intense market competition (9%) and the lack of policy support (6%). As Jessore contributes fifty percent of total fry and fingerling production in Bangladesh, therefore, the stakeholders should focus on the trade issues, otherwise fish supply would be interrupted as a whole. DOI: http://dx.doi.org/10.3329/pa.v18i2.19197 Progress. Agric. 18(2): 199 - 207, 2007